1996
DOI: 10.1148/radiology.201.2.8888257
|View full text |Cite
|
Sign up to set email alerts
|

Anemia is associated with lower local-regional control and survival after radiation therapy for head and neck cancer: a prospective study.

Abstract: Moderate anemia appeared to be an independent prognostic factor in squamous cell carcinoma of the head and neck treated with radiation therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 0 publications
3
90
1
4
Order By: Relevance
“…In this study, those with anemia had functional, not physiologic, anemia. All but 3 of 63 patients with anemia-defined as hemoglobin <13.5 g/dl for men and hemoglobin <12.0 g/dl for women-had hemoglobin >10 g/dl [17]. Because most of our patients also had anemia that was modest and "functional," we believe the same opportunities exist to improve outcomes.…”
Section: Understanding the Impact Of Anemiamentioning
confidence: 84%
“…In this study, those with anemia had functional, not physiologic, anemia. All but 3 of 63 patients with anemia-defined as hemoglobin <13.5 g/dl for men and hemoglobin <12.0 g/dl for women-had hemoglobin >10 g/dl [17]. Because most of our patients also had anemia that was modest and "functional," we believe the same opportunities exist to improve outcomes.…”
Section: Understanding the Impact Of Anemiamentioning
confidence: 84%
“…Other studies have shown a statistically significant association between anaemia and reduced local control or survival in cervical cancer or head and neck cancer (Fein et al, 1995;Dubray et al, 1996;Warde et al, 1998;Grogan et al, 1999). Dubray et al (1996) found that even moderate anaemia significantly correlated with a worse treatment outcome in squamous cell carcinoma of the head and neck (Figure 2). However, it is unclear whether low haemoglobin directly contributes to reduced tumour control and survival after radiotherapy, or whether it is merely a marker of advanced disease in patients for whom successful treatment outcomes are less likely, regardless of tumour oxygenation.…”
Section: Possibilities For Improved Treatment Outcomesmentioning
confidence: 87%
“…Many studies have found that inadequate oxygenation at the tumour site and/or low haemoglobin values are associated with poor treatment outcome after curative radiotherapy (Fein et al, 1995;Dubray et al, 1996;Fyles et al, 1998;Grogan et al, 1999). Adequate tumour oxygenation is known to be necessary for an optimal response to radiotherapy (Glaspy and Cavill, 1999), thus it is theoretically possible that decreased haemoglobin (which may contribute to lowered oxygenation at the tumour site) may also have an effect on the success of therapy.…”
Section: Possibilities For Improved Treatment Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the literature concerns malignancies of the uterine cervix (Evens and Bergso, 1965;Hierlihy et al, 1969;Vigerio et al, 1973;Bush et al, 1978;Dische et al, 1983;Mendenhall et al, 1984;Bush, 1986;Girinski et al, 1989;Rader, 1990) and head and neck (Blitzer et al, 1984;Overgard et al, 1989;Dubray et al, 1996). How anaemia is causally related to poor outcome is not entirely clear but it is probably both a marker of advanced tumour and indicative of some degree of tissue hypoxia.…”
Section: Discussionmentioning
confidence: 99%